2018
DOI: 10.3762/bjnano.9.70
|View full text |Cite
|
Sign up to set email alerts
|

Surface-plasmon-enhanced ultraviolet emission of Au-decorated ZnO structures for gas sensing and photocatalytic devices

Abstract: Pure and Au-decorated sub-micrometer ZnO spheres were successfully grown on glass substrates by simple chemical bath deposition and photoreduction methods. The analysis of scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images, energy-dispersive X-ray spectroscopy (EDS), UV–vis absorption, and photoluminescence (PL) spectra results were used to verify the incorporation of plasmonic Au nanoparticles (NPs) on the ZnO film. Time-resolved photoluminescence (TRPL) spectra indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…It is noticed that the viability of HT 144 cells reduces remarkably by treating with ZnO:Ag(10%) of various concentrations under visible light ( Figure 35 b). The AgNPs dopant facilitates the formation of •O 2− and •OH radicals on ZnO due to the plasmonic oscillation of free electrons under visible light as mentioned previously ( Figure 7 a) [ 69 , 70 , 71 , 72 ]. So, the ROS production efficacy of ZnO:Ag(10%) is considerably higher than that of pure ZnO under visible light illumination.…”
Section: Cytotoxicitymentioning
confidence: 61%
See 2 more Smart Citations
“…It is noticed that the viability of HT 144 cells reduces remarkably by treating with ZnO:Ag(10%) of various concentrations under visible light ( Figure 35 b). The AgNPs dopant facilitates the formation of •O 2− and •OH radicals on ZnO due to the plasmonic oscillation of free electrons under visible light as mentioned previously ( Figure 7 a) [ 69 , 70 , 71 , 72 ]. So, the ROS production efficacy of ZnO:Ag(10%) is considerably higher than that of pure ZnO under visible light illumination.…”
Section: Cytotoxicitymentioning
confidence: 61%
“…This collective electron oscillation causes a charge separation at particle surface with respect to positively charged metallic core ( Figure 6 b) [ 68 ]. SPR absorption induces rapid heating of metal NPs under visible light [ 69 , 70 , 71 ]. So, SPR-generated hot electrons are injected to the CB of ZnO, generating superoxide anion through a surface reaction with adsorbed oxygen, and its subsequent conversion to hydroxyl radical ( Figure 7 a) [ 72 ].…”
Section: Structure-dependent Photocatalytic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the PL intensity of ZnO NRs at 382 nm can be increased up to 25 times by decoration with Cr NPs [25]. Similarly, a significant PL enhancement was observed followed decoration with Pt, Au and Ag NPs [26][27][28][29].…”
Section: Introductionmentioning
confidence: 88%
“…The photo-electrons in the conduction band react with O2 to produce a superoxide radical anion O2 -* , while the photogenerated holes in the valence band react with surface hydroxyl ion OHor H2O molecules to produce a OH -* radical. These O2 -* and OH -* radicals are active oxidants, which can oxidize adsorbed molecules such as rhodamine 6G [37,38], rhodamine B [26,39], methylene blue [40], benzene [41]. In studying the photocatalytic oxidation of glucose in water, Cheng et at.…”
Section: Glucose and H2o2 Sensing Of The Zno Nrs/au Nps Based Fluorescent Sensormentioning
confidence: 99%